Clinical Profile, Transmission Factors, and Early Disability Prevalence of Leprosy: A Single Center Observational Study at Bunda Pembantu Abadi General Hospital Naob, East Nusa Tenggara, Indonesia - Ayleen Nathalie Jap; Hawari, Irawaty (Community Medicine and Education Journal, 2024)
Leprosy is a chronic granulomatous infectious disease that causes peripheral neuropathy with disabling manifestations. This disease is caused by Mycobacterium leprae, which thrives in cool body surface temperatures and enters the body through the nose and skin. This study aims to identify the clinical profile of leprosy patients, risk factors for transmission, and the prevalence of early disability. This research uses a cross-sectional approach with descriptive methods. This study was conducted in December 2023 at the Bunda Pembantu Abadi General Hospital, involving 130 leprosy patients who met the inclusion criteria. Data was collected using medical record data, including gender, age, occupation, family history, marital status, number of children, vital signs, duration of illness, WHO disability level score, bacterial index, and morphological index. Most of the respondents were men with normal vital signs except for body temperature, positive bacterial index, solid morphology index on the forehead, ear lobes and chin, and had a disability prevalence of 0 of 43.1% (56/130) because leprosy patients had a long illness. for one year. In conclusion, the clinical profile of leprosy patients at this hospital is dominated by men of productive age. The low rate of early disability highlights the importance of early detection and treatment. Further research is needed to understand risk factors for transmission and preventive interventions.